Epigenetic Activation of ASCT2 in the Hippocampus Contributes to Depression-Like Behavior by Regulating D-Serine in Mice - Wang, Jiesi; Zhang, Ke; Chen, Xiaojuan; Liu, Xiaoqian; Teng, Huajing; Zhao, Mei; Sun, Zhongsheng (Frontiers in Molecular Neuroscience, 2017)
The roles of D-serine，an intrinsic co-agonist for the NMDA receptor， in depression are raised concerned recently. However, the mechanisms underlying its regulation are not fully elucidated. ASCT2 is a Na+-dependent D-serine transporter. We found that decreased D-serine and increased hippocampal ASCT2 levels correlated with chronic social defeat stress (CSDS) in mice. Lentivirus-mediated shRNA-mediated knockdown of ASCT2 and the administration of exogenous D-serine in the hippocampus alleviated CSDS-induced social avoidance and immobility. In vivo and in vitro experiments revealed that upregulation of ASCT2 expression in CSDS was regulated through histone hyper-acetylation, not DNA methylation in its promoter region. Immunohistochemistry demonstrated the co-localization of ASCT2 and D-serine. Uptake of D-serine by ASCT2 was demonstrated by in vivo and in vitro experiments. Our results indicate that CSDS induces ASCT2 expression through epigenetic activation and decreases hippocampal D-serine levels, leading to social avoidance and immobility. Thus, targeting D-serine transport represents an attractive new strategy for treating depression.